Predictive Value of the sFlt-1/PlGF Ratio and Interleukin-6 for the Presence of Placental Lesions in Spontaneous Preterm Labor with Intact Membranes with Delivery within 7 Days - Kacerovsky, Marian; Hornychova, Helena; Holeckova, Magdalena; Pavlikova, Ladislava; Rezabkova Chloubova, Jitka; Jacobsson, Bo; Musilova, Ivana (Fetal diagnosis and therapy, 2024)
INTRODUCTION: The aim of the study was to identify predictive values of the soluble fms-like tyrosine kinase/placental growth factor (sFlt-1/PlGF) ratio and interleukin (IL)-6, assessed with a clinically available method in a large-volume biochemistry laboratory, in maternal blood, amniotic fluid, and umbilical cord blood for the presence of the placental lesions consistent with maternal vascular malperfusion (MVM) and acute histological chorioamnionitis (HCA), respectively. METHODS: This retrospective study included 92 women with preterm labor with intact membranes (PTL) delivered within 7 days of admission with gestational ages between 22+0 and 34+6 weeks. The sFlt-1/PlGF ratio and IL-6 were assessed in stored samples of maternal serum, amniotic fluid, and umbilical cord serum using Elecsys® sFlt-1, PlGF, and IL-6 immunoassays. RESULTS: Women with MVM had a higher sFlt-1/PlGF ratio in the maternal serum, compared to those without MVM (19.9 vs. 4.6; p < 0.0001), but not in the amniotic fluid or umbilical cord blood. A cut-off value of 8 for the sFlt-1/PlGF ratio in maternal serum was identified as optimal for predicting MVM in patients with PTL. Women with HCA had higher concentrations of IL-6 in maternal serum, compared to those without HCA (11.1 pg/mL vs. 8.4 pg/mL; p = 0.03), amniotic fluid (9,216 pg/mL vs. 1,423 pg/mL; p < 0.0001), and umbilical cord blood (20.7 pg/mL vs. 10.7 pg/mL, p = 0.002). Amniotic-fluid IL-6 showed the highest predictive value. A cut-off value of IL-6 concentration in the amniotic fluid of 5,000 pg/mL was found to be optimal for predicting HCA in PTL. CONCLUSION: Maternal serum sFlt-1/PlGF and amniotic fluid IL-6 concentrations can be used for liquid biopsy to predict placental lesions in women with PTL who deliver within 7 days.
Keywords: Pregnancy; Humans; Placenta Growth Factor; předčasná porodní činnost; Predictive Value of Tests; Placenta; Female; Interleukin-6; Vascular Endothelial Growth Factor Receptor-1; dospělí; lidé; chorioamnionitida; Biomarkers; Amniotic Fluid; receptor 1 pro vaskulární endoteliální růstový faktor; Fetal Blood; Adult; Obstetric Labor, Premature; ženské pohlaví; biologické markery; fetální krev; plodová voda; interleukin-6; prediktivní hodnota testů; Retrospective Studies; těhotenství; Chorioamnionitis; retrospektivní studie; placentární růstový faktor; placenta